The peacebuilding puzzle : political order in post-conflict states - Barma, Naazneen (Cambridge ; New York : Cambridge University Press, 2017)
"This book explains why international post-conflict interventions have fallen short of the weighty aspirations they embody. It reframes the peacebuilding puzzle by presenting a new theory of how domestic elites construct political order during and after peacebuilding interventions. A comparative analysis of the UN's transformative peacebuilding attempts in Cambodia, East Timor, and Afghanistan shows that while international peacebuilders want to build effective and legitimate government, domestic elites essentially do not. As is the case in much of the developing world, post-conflict elites use strategies to prioritize their own political survival and power that result in a neopatrimonial political order that better delivers on their goals. Peacebuilding interventions thus generate a set of unintended yet predictable effects. In all three cases, the UN's efforts at peacebuilding through elite settlement followed by a process of simultaneous statebuilding and democratization were co-opted by a small subset of domestic power-holders who successfully closed down the political space and stunted state capacity. To be sure, each of these countries is better off than before the peace operations. Yet the goals of intervention have not truly been met. Instead, there are striking similarities in the patterns of neopatrimonial order that emerge in the aftermath of intervention. This book makes the case that the peacebuilding approach is, at least in part, itself responsible for the eventually disappointing governance outcomes that emerge in post-conflict countries"--
Includes bibliographical and index.
Description based on print version record; resource not viewed.
Keywords: United Nations -- Peacekeeping forces -- Case studies; Conflict management -- Developing countries; Peace-building.; POLITICAL SCIENCE / General; Peacekeeping forces -- Developing countries